Pharmacology education for nurse prescribing students - a lesson in reusable learning objects - Bath-Hextall Fiona; Lymn Joanne S; Wharrad Heather J (BMC, 2008)
Abstract Background The shift away from a biological science to a social science model of nursing care has resulted in a reduction in pharmacology knowledge and understanding in pre-registration nursing students. This has a significant impact on nurse prescribing training where pharmacology is a critical component of the course from a patient safety perspective. Methods Reusable learning objects (RLOs) are electronic resources based on a single learning objective which use high quality graphics and audio to help engagement with the material and to facilitate learning. This study used questionnaire data from three successive cohorts of nurse prescribing students (n = 84) to evaluate the use of RLOs focussed around pharmacology concepts to promote the understanding of these concepts in students. A small number of students (n = 10) were followed up by telephone interview one year after qualification to gain further insight into students' perceptions of the value of RLOs as an educational tool. Results Students' perceptions of their own understanding of pharmacology concepts increased substantially following the introduction of RLOs to supplement the pharmacology component of the course. Student evaluation of the RLOs themselves was extremely positive with a number of students continuing to access these tools post-qualification. Conclusion The use of RLOs to support the pharmacology component of nurse prescribing courses successfully resulted in a perceived increase in pharmacology understanding, with some students directly implicating these educational tools in developing confidence in their own prescribing abilities.